The Urgency of Regulating Provisions That Cannot Be Changed in Amendments to the Indonesian Constitution: Urgensi Pengaturan Ketentuan Tidak Boleh Diubah Dalam Amandemen Konstitusi Indonesia - Ibra Fulenzi Amri; Tundjung Herning Sitabuana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Since the Reform Era, Indonesia has undergone extensive political and constitutional transformation that renewed demands to reorganize national governance through amendments to the 1945 Constitution. Specific Background: The re-emergence of constitutional amendment discourse after 27 years of Reform raises concerns about unstructured changes that may weaken constitutional authority and threaten national integrity. Knowledge Gap: Indonesia has not yet established explicit constitutional provisions identifying which foundational norms must remain unamendable. Aims: This study aims to formulate a normative framework for determining non-amendable constitutional provisions to ensure orderly amendments and preserve constitutional stability. Results: The findings show that the MPR must adopt fundamental agreements protecting the following from amendment: the Preamble, the state ideology, the goals of the state, the form of the state, the separation of powers under checks and balances, human rights guarantees, and procedures for constitutional amendment in emergencies. Comparative analysis shows that many countries, including Germany, France, Portugal, Spain, and Turkey, maintain similar immutable clauses. Novelty: This study offers a comprehensive normative construction of unamendable provisions within Indonesia’s constitutional framework. Implications: Explicitly regulating immutable constitutional clauses is essential to safeguard constitutional supremacy and prevent national disintegration. Highlights: Identifies core constitutional elements that must remain unamendable to preserve state integrity. Highlights the need for structured and principled constitutional amendment procedures. Shows that Indonesia aligns with global constitutional practices protecting foundational norms. Keywords: Constitutional Amendment, Unamendable Provisions, Constitutional Stability, Indonesia, Constitutional Law